1993
DOI: 10.7547/87507315-83-4-198
|View full text |Cite
|
Sign up to set email alerts
|

Navicular drop as a composite measure of excessive pronation

Abstract: The measure of navicular drop has been used as an indicator of pronation at the foot. It is defined as the distance the navicular tuberosity moves in standing, as the subtalar joint is allowed to move from its neutral position to a relaxed position. The purposes of this study were to test the reliability of a method to measure navicular drop and to assess the relationships among measures of forefoot to rearfoot position, subtalar joint neutral position, and navicular drop. The results support traditional biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
2
10

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 0 publications
6
117
2
10
Order By: Relevance
“…The intrarater reliability of the navicular drop test was previously reported, with ICCs between 0.61 and 0.79, 68,73,86 whereas interrater reliability ranged from 0.46 to 0.83. 25,73,86,87 The validity agreement of the navicular drop test with values calculated from radiographs through radio-opaque markers affixed at the surface anatomical landmarks had good Pearson correlation coefficients (between 0.61 and 0.89).…”
Section: Discussionmentioning
confidence: 99%
“…The intrarater reliability of the navicular drop test was previously reported, with ICCs between 0.61 and 0.79, 68,73,86 whereas interrater reliability ranged from 0.46 to 0.83. 25,73,86,87 The validity agreement of the navicular drop test with values calculated from radiographs through radio-opaque markers affixed at the surface anatomical landmarks had good Pearson correlation coefficients (between 0.61 and 0.89).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria included a history of a lower extremity injury up to six months prior to participation and excessive pronation determined by the ND. Excessive pronation was defined as a ND of >10 mm, similar to previous studies8, 12 ) . This study was approved by the Ethics Committee of the Prefectural University of Hiroshima (Approval Number: 15MH027), and written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 87%
“…However, in these studies a navicular drop test (ND) was used to measure the change in the MLA height. The ND was performed by manually using a caliper, and the standard error of the ND was reported to be 1.68–2.57mm8, 9 ) . So there is some doubt that the ND was an appropriate method to measure a 2–3 mm change in the MLA height in an experimental design that did not allow for a blinding of the examiner to the weakening status of the intrinsic foot muscles.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Various authors have suggested a drop of 10 to 15 mm as abnormal. 16,17 In this study, anything greater than a 10 mm drop was considered abnormal. Figure 1 and Table 1, an independent t-test (inter-group) revealed a statistically significant decrease (p Յ 0.05) in ankle dorsiflexion ROM in individuals with chronic mechanical low back pain (intervention group) in comparison to individuals without low back pain (control group) in both the right and left feet (p = 0.002 and p = 0.032 respectively).…”
Section: Measurementmentioning
confidence: 99%